Trump administration is threatening liberal foundations and nonprofits after Kirk’s death – but proving wrongdoing by any of them would be very hard - Gazley, Beth (The Conversation U.S, 2025)
When foundations provide grants, they’re engaging in a protected free speech activity that entitles them to certain privacy rights.